A Cross-Modal Perspective on the Relationships between Imagery and Working Memory - Likova, Lora T. (Frontiers in Psychology, 2013)
Mapping the distinctions and interrelationships between imagery and working memory remains challenging. Although each of these major cognitive constructs is defined and treated in various ways across studies, most accept that both imagery and working memory involve a form of internal representation available to our awareness. In working memory, there is a further emphasis on active maintenance and use of this conscious representation to guide voluntary action. Multicomponent working memory models incorporate representational buffers, such as the visuo-spatial sketchpad, plus central executive functions. If there is a visuo-spatial ‘sketchpad’ for working memory, does imagery involve the same representational buffer? Alternatively, does working memory employ an imagery-specific representational mechanism to occupy our awareness? Or do both constructs utilize a more generic ‘projection screen’ of an amodal nature? In a cross-modal fMRI study a novel memory paradigm is introduced based on drawing, which may be conceptualized as a complex behaviour adaptable to learning in the tactile modality. Blindfolded participants were trained to draw complex objects guided purely by the memory of felt tactile images. If this working memory task had been mediated by transfer of the felt spatial configuration to the visual imagery mechanism, the response profile in visual cortex would be predicted to have the ‘top-down’ signature of propagation of the imagery signal downwards through the visual hierarchy. Remarkably, the pattern of cross-modal occipital activation generated by the non-visual memory drawing was essentially the inverse of this typical ‘imagery signature’, with the sole visual hierarchy activation occurring in V1, accompanied by deactivation of the entire extrastriate part of the hierarchy. The implications of these findings for the debate on the interrelationships between the core cognitive constructs of working memory and imagery are evaluated.